Non-Hodgkin's lymphoma: a preliminary morphometric study - Aiad Abdullah Abdulrazak (Asian Journal of Medical Research, 2017)
Objectives: Assessment of nuclear morphology is crucial for the diagnosis of non-Hodgkin's lymphoma. However, it is often hampered by subjectivity and inter-obsever variation. This work is aimed at studying the usefulness of nuclear morphometry as an objective approach to the diagnosis of non-Hodgkin's lymphoma. Methods: Hematoxylin-Eosin stained sections from twenty-eight cases of non-Hodgkin's lymphoma was evaluated for nuclear size, area and perimeter by semi-automated image analysis system. Results: The parameters related to nuclear morphology (nuclear size, area, & perimeter) of neoplastic lymphocytes were significantly higher in large cell lymphoma as compared to small cell, intermediate cell & Burkitt's lymphoma but, not for mixed cell lymphoma.This finding was further substantiated when calculating the overlap index. Conclusion: This study supports the assumption that nuclear morphometryoffers a more objective and reproducible diagnostic method for subcategorizing lymphoid tumors than is currently possible by conventional histopathological techniques.